Predictive factors for Peritoneal Dialysis Catheter Survival: a ten-year single center study - Bárbara Beirão Rodrigues; Mariana Freitas; João S. Borges; Beatriz Pereira; Catarina Prata; Rui Castro; Teresa Morgado (Bulletin de la Dialyse à Domicile)
Introduction and Objectives: Timely insertion and adequate management of peritoneal dialysis catheter (PDC) related complications are crucial for the success of Peritoneal Dialysis. The aim of this study was to review the peritoneal dialysis catheter outcomes at our center, identifying factors that influence catheter survival.